Quality of Nursing Care in Saudi Arabia: Are Empathy, Advocacy, and Caring Important Attributes for Nurses? - Alsufyani, Abdulaziz M.; Aldawsari, Abdulaziz A.; Aljuaid, Sayer M.; Almalki, Khalid E.; Alsufyani, Yasir M. (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: The examination of the literature indicates that practicing nurses are barely engaged in developing enhancement programs for quality nursing care. There are numerous studies on the value of nursing care, but none offers ways of assessing the value of care provided by nurses. Identifying the essence of quality nursing care can facilitate effective enhancement approaches. It was prudent to explore the relationship between advocacy, caring, and empathy in delivering quality nursing care.Purpose: This study aimed to comprehend the views of Saudi Arabian nurses on how empathy, advocacy, and caring act as measurements of quality of nursing care.Methods: A qualitative investigative, descriptive design was used to explore the advocacy, empathy, and caring from the viewpoints of practicing nurses. Twenty-one general and specialized medical care nurses from King Saud Medical City in Saudi Arabia were recruited through purposive sampling. The researchers conducted semi-structured interviews that were recorded, written out, and subjected to thematic analysis.Results: The findings have led to the establishment of quality Saudi nursing care with the identification of core themes: empathy, advocacy, and caring. The findings of this study elevate the understanding of the quality of nursing care in the Saudi context.Conclusion: The participants aver that patient advocacy, empathy, and care are parts of the characteristics of nursing profession. These characteristics aid in listening and comprehending patients’ perspectives. Following the findings, it is suggested to provide training to the nurses to overcome the challenges faced by nurses in reflecting empathy.